Respon Global Terhadap Dominasi Ekonomi China - Melaty Anggraini (Jurnal Paradigma, 2019)
The Resurgence of Economic China started from strategic Deng xiao ping Era,which is open reformation era and, the open policy becomes foster of the growth of economic China. Even though it needed a difficult long process for the growth of the economic system, china can prove and become a developing country which had label “Newly Industrialized Countries.” A Resurgence of Economic China caused the domination effect for countries surrounded, and suspicious for them so caused response from another country. Response who is got China more to anticipated way cause many countries think China will make expansion economic. For response that needs disruption mindset so every country didn’t scrape with issues economic and international trade how can more weaken position country which had a cooperationwith China in the global economic politic system. For that, the author invited readersfor an understanding of the way to responses resurgence of economic China to handle and can get benefit from the economic growth of China.